‘Sami Religion’ in Sámi Curricula in RE in the Norwegian School System: An Analysis of the Importance of Terms - Bengt-Ove Andreassen; Torjer A. Olsen (Religions, 2020)
In this article, we map and analyse the changes in conceptualisation and ideas on Sámi and indigenous people in the Sámi (Religious Education) RE curricula for primary and secondary school in the period from 1997 to 2015. Through the analysis of five sets of curricula for RE in this period, we investigate how they introduce a new set of ideas and concepts concerning religion related to the Sámi as an indigenous people. ‘Circumpolar indigenous people’s religion’ is a concept and a category that is primarily found within the Sámi curriculum of Norway’s educational system. As such, we argue it is a way of religion making through the conceptualization of Sámi religion in particular, and indigenous religions in general.